A quantitative review of pollination syndromes: do floral traits predict effective pollinators?. (7th January 2014) - Rosas‐Guerrero, Víctor; Aguilar, Ramiro; Martén‐Rodríguez, Silvana; Ashworth, Lorena; Lopezaraiza‐Mikel, Martha; Bastida, Jesús M.; Quesada, Mauricio; Irwin, Rebecca
Abstract The idea of pollination syndromes has been largely discussed but no formal quantitative evaluation has yet been conducted across angiosperms. We present the first systematic review of pollination syndromes that quantitatively tests whether the most effective pollinators for a species can be inferred from suites of floral traits for 417 plant species. Our results support the syndrome concept, indicating that convergent floral evolution is driven by adaptation to the most effective pollinator group. The predictability of pollination syndromes is greater in pollinator‐dependent species and in plants from tropical regions. Many plant species also have secondary pollinators that generally correspond to the ancestral pollinators documented in evolutionary studies. We discuss the utility and limitations of pollination syndromes and the role of secondary pollinators to understand floral ecology and evolution.